2019
DOI: 10.1007/s10695-019-00713-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of industrial pollution on the reproductive biology of Squalius laietanus (Actinopterygii, Cyprinidae) in a Mediterranean stream (NE Iberian Peninsula)

Abstract: Mediterranean rivers are severely affected by pollutants from industry, agriculture and urban activities. In this study we examined how industrial pollutants, many of them known to act as endocrine disruptors (EDCs), could disturb the reproduction of the Catalan chub (Squalius laietanus). The survey was conducted throughout the reproductive period of S. laietanus (from March to July 2014) downstream an industrial WWTP located in the River Ripoll (NE Iberian Peninsula). Eighty fish (28 females and 52 males) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 63 publications
(76 reference statements)
1
11
0
Order By: Relevance
“…Comparisons of baseline enzymatic activities were made in fish sampled in a confirmed reference area, all considering the undeniable anthropogenic fingerprint of NW Mediterranean watercourses (Blanco et al 2019;Carbajal et al 2019;Colin et al 2016b;Maceda-Veiga et al 2013;Marqueño et al 2019;Soler et al 2020). Markers of neurotoxicity signs (AChE), protection (BuChE), energy metabolism (LDH and CS),…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparisons of baseline enzymatic activities were made in fish sampled in a confirmed reference area, all considering the undeniable anthropogenic fingerprint of NW Mediterranean watercourses (Blanco et al 2019;Carbajal et al 2019;Colin et al 2016b;Maceda-Veiga et al 2013;Marqueño et al 2019;Soler et al 2020). Markers of neurotoxicity signs (AChE), protection (BuChE), energy metabolism (LDH and CS),…”
Section: Discussionmentioning
confidence: 99%
“…xenobiotic metabolism and antioxidant defences (Colin et al 2016a) were selected as suggestive of a particular microhabitat use and biochemical adaptation. Since fish were simultaneously sampled at the same site, physical and chemical water conditions (described in Soler et al 2020) and the ecological characteristics of the habitat were common and only the influence of the particular diet, habitat use and physiological traits of each species will dictate the differences observed. In fact, the analysis of PFAS revealed higher bioaccumulation in barbel as formerly described for other organic contaminants and metals in the same fish species from the same geographical area From a biochemical perspective, the relationship between baseline enzymatic activities and in vitro sensitivity to chemicals can provide an estimation of the fish susceptibility to xenobiotics (Sanchez-Nogue et al 2013;Ribalta et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ammonia is not the only pollutant present at these two sites, it is one of the most frequently found, not only in this river but in all rivers of NE Spain [2]. Table 1 shows the physical-chemical parameters analyzed at the two sites for the sampling month for Granollers Town Council (polluted site) and Fortuño et al [32] (unpolluted site). Other contaminants such as contaminants of emerging concern (CEC) (pesticides, metals, industrial solvents, pharmaceuticals and personal care products), could be found in other sites across these basin [32].…”
Section: Methodsmentioning
confidence: 99%